2021
DOI: 10.1038/s41598-021-82132-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventive efficiency of Cornelian cherry (Cornus mas L.) fruit extract in diniconazole fungicide-treated Allium cepa L. roots

Abstract: Cornelian cherry (Cornus mas L.) is a medicinal plant with antioxidant-rich fruits. Diniconazole, a broad-spectrum fungicide, is employed extensively. The present study was designed to evaluate the preventive efficiency of C. mas fruit extract (CME) against the toxic effects of diniconazole on a model organism, Allium cepa L. For this aim, physiological, cytogenetic and biochemical parameters as well as the meristematic cell damages were investigated in A. cepa treated with diniconazole and C. mas extract. A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Macar et al 54 reported that the application of 125 mg/L fenpyroximate caused deformation in the epidermis, flattening of the cell nucleus and damage in the conduction tissue in A. cepa root tip meristem cells. Kalefetoğlu Macar et al 15 observed that the administration of a 100 mg/L dose of diniconazole promoted epidermis cell deformation, thickening of the cortex cell wall, flattened cell nuclei and unclearly vascular tissue damage in A. cepa root tip cells. In this study, it is thought that the damage to root meristem cells as a result of exposure to metaldehyde is caused by the defense mechanisms developed by the cells to prevent metaldehyde from being absorbed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macar et al 54 reported that the application of 125 mg/L fenpyroximate caused deformation in the epidermis, flattening of the cell nucleus and damage in the conduction tissue in A. cepa root tip meristem cells. Kalefetoğlu Macar et al 15 observed that the administration of a 100 mg/L dose of diniconazole promoted epidermis cell deformation, thickening of the cortex cell wall, flattened cell nuclei and unclearly vascular tissue damage in A. cepa root tip cells. In this study, it is thought that the damage to root meristem cells as a result of exposure to metaldehyde is caused by the defense mechanisms developed by the cells to prevent metaldehyde from being absorbed.…”
Section: Resultsmentioning
confidence: 99%
“…Allium cepa has become one of the most used model organisms in plant-based toxicity studies due to its large sized and small number of chromosomes that can be easily seen under light microscopy, easy accessibility, low cost, reliability and high correlation with other test systems 15 , 16 . Allium assay has been used for many years to elucidate the genotoxic effects of pesticides in living organisms 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%